Perhitungan Dan Peletakkan Denah Alat Pemadam Api Ringan Sebagai Tindakan Pencegahan Kebakaran - Anggita Puspa Wardhani; Nur Ruroh Hayyu S.W; Aisyah Marlidah; Ahda Azizah (Universitas Pahlawan Tuanku Tambusai, 2024)
Fire is an event that is often sudden and can cause major losses, both in terms of property and life. Fires can occur in various places, from residential homes, office buildings, to forests and open land. So a safety system is needed that can provide assistance as quickly as possible for dangerous situations that occur at any time. Apart from that, the safety system must be designed as well as possible so that when an emergency occurs it can be used according to its function and provide maximum assistance. To minimize the risk of fire, it is necessary to have a fire protection safety system that is available in a planned manner, especially one that is installed and absolutely must be observed. Therefore, what needs to be done is to create a light fire prevention system using light fire extinguishers in every building in the Company. The method used in this research is systematic steps by obtaining data obtained from the internet, journals and existing regulations. The results of this research are in the form of calculations and placement of APARs in one building